A Region at Risk: Opportunities, Gaps, and Challenges for Social Disaster Research in Central America - Cabrales Domínguez, Sergio (2025)
Central America is a region with multiple and growing risks from natural disasters. This study reviews how social sciences, mainly in the US and Central America, have approached the study of the issue in the isthmus. It finds considerable attention to long-standing events but insufficient research on recent disasters. Thanks to the regression analysis of data from the LAPOP 2021 survey, this paper confirms the validity and relevance of the topic. For example, it finds that the most vulnerable Central Americans have a greater risk perception and have suffered more from these events. The social study of Central American disasters has the potential to facilitate transnational and transdis-ciplinary dialogues and challenge the understanding of these events at a global level.